Seven or Fewer Core Contents of Social Responsibility? - Mira Zore; Majda Bastič; Matjaž Mulej (Naše gospodarstvo/Our economy, 2016)
Corporate social responsibility (CSR) replaces causes of the current crisis by principles of accountability, transparency, ethics, and respect for organizational stakeholders, the law, international standards, and human rights (International Organization for Standardization, 2010). Interdependence and a holistic approach link them and CSR’s core contents. We examined if Slovene companies involve all seven CSR core contents of ISO 26000 (CSR to employees, customers, local community, environment, human rights, ethical behavior, and leadership). The analysis united three of them—CSR to employees, ethical behavior, and human rights—into CSR leadership to employees.